A modular switched-capacitor multilevel inverter featuring voltage gain ability - Wang, Yaoqiang; Ye, Juncheng; Ku, Ruohan; Shen, Yuchen; Li, Gen; Liang, Jun (JOURNAL OF POWER ELECTRONICS, 2023)
This article presents a modular switched-capacitor multilevel inverter which uses two capacitors and a single dc source to obtain triple voltage gain. It is worth noting that the inherent inversion capacity removes the H-bridge, which can efficaciously diminish the voltage stress of switches, and the maximum voltage stress (MVS) on devices is kept within 2 V dc . Additionally, the proposed topology is able to integrate inductive load, and the capacitor voltage self-balancing can be achieved. Moreover, the modular structure also has an expandable topology which can generate more levels and raise the voltage gain by using multiple switched-capacitor units, meanwhile the voltage stress on power switches can be kept within 2 V dc . Furthermore, comprehensive analysis and comparison with other multilevel inverters have been implemented to certify the superiority of the proposed topology. Finally, the steady-state and dynamic performance of the proposed topology is examined through a seven-level inverter prototype, the validity and practicability of the topology are verified by simulations and experiments.